APPLIABLE PROVISIONS OF THE CONSTITUTION IN THE SOCIAL ASSISTANCE FIELD - Laura, Voiculescu Cetean (Anales Universitatis Apulensis Series Jurisprudentia, 2012)
This paper aims at analyzing the constitutional provisions applicable in the field of social assistance. Legal rules laid down by the Constitution are essential or constitutional, the other rules contained in other legislation are unsubstantiated or ordinary, shall be in accordance with those contained in the Constitution. Their importance, we will present those with implications for social assistance. Keywords : constitutional provisions, social assistance, Constitution, Legal rules, the right to identity, unity and solidarity.